The size distribution across all "cities": A unifying approach - Kristian Giesen; Jens Suedekum (Institute for the Study of Labor (IZA), 2012)
In this paper we show that the double Pareto lognormal (DPLN) parameterization provides an excellent fit to the overall US city size distribution, regardless of whether cities are administratively defined Census places or economically defined area clusters. We then consider an economic model that combines scale-independent urban growth (Gibrat's law) with endogenous city creation. City sizes converge to a DPLN distribution in this model, which is much better in line with the data than previous urban growth frameworks that predict a lognormal or a Pareto city size distribution (Zipf's law).
urn:nbn:de:101:1-201205026189
Keywords: R11; R12; O4; 330; Zipf's law; Gibrat's law; city size distributions; double Pareto-Lognormal; Stadtgröße; Statistische Verteilung; Stadtwachstum; Schätzung; USA